Determination of the process variables for adsorption and desorption of phosphate from wastewater by selective ion exchangers on magnetic particles - Jiménez Gutiérrez, Yamileth Milena (2015)
El informe de investigación fue supervisado por Dr.-Ing. Asya Drenkova-Tuhtan y examinado por Dr.-Ing. Heidrun Steinmetz.